Environment carrying capacity and willingness to pay for bird-watching ecotourism in Kerandangan Natural Park, Lombok, Indonesia - I Wayan Suana; Hilman Ahyadi; Gito Hadiprayitno; Saleh Amin; Lalu Achmad Tan Tilar Wangsajati Sukmaring Kalih; Franciscus Xaverius Sudaryanto (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Suana IW, Ahyadi H, Hadiprayitno G, Amin S, Kalih LATTWS, Sudaryanto FX. 2020. Environment carrying capacity and willingness to pay for bird-watching ecotourism in Kerandangan Natural Park, Lombok, Indonesia. Biodiversitas 21: 2266-2274.  Five trails of interest to bird-watchers and an observation point by the guest house of Kerandangan Natural Park (KNP) have potential to be developed as bird-watching ecotourism packages. In order to develop sustainable bird-watching ecotourism in KNP, we analyzed the environment carrying capacity and willingness to pay (WTP) for bird-watching ecotourism packages. All of the trails and an observation point in KNP were explored to determine the width and length of the trails, the visit time, as well as the soil texture and slope along the trails. Interviews with KNP managers and secondary data from Meteorology, Climatology and Geophysics Council (BMKG)-Climatology Station Class I-West Lombok were also used to determine the status of biophysical habitats. The environment carrying capacity was calculated by combining the physical carrying capacity, real carrying capacity, and effective carrying capacity. The results show that environment carrying capacity of bird-watching ecotourism packages in KNP was higher than the actual visitation levels. It indicates that opportunity to develop and increase the number of visitors is considerable. WTP was determined by Contingent Valuation Method (CVM) with payment card approach. Through the brochure, 150 respondents were given information on bird-watching ecotourism packages, then are offered three options, and only allowed to choose one that can be paid. Data were collected by the incidental sampling method. The results show that the visitors are willing to pay for bird-watching ecotourism packages, with mean WTP of US$ 20.7 per visitor. It implies that they are willing to shoulder the financial support for management and conservation of birds and their habitat in KNP. The findings provide important information for KNP managers for planning and marketing bird-watching ecotourism in KNP.